Rethinking Subsidiary in Corruption Cases: Indonesian Experiences - Nugroho, Fendi; Hartiwiningsih, Hartiwiningsih; I Gusti Ayu Ketut Rachmi Handayani (Journal of Human Rights, Culture and Legal System, 2025)
The imposition of additional penalties in the form of restitution in corruption cases in Indonesia continues to reveal significant conceptual and practical weaknesses. A primary issue is the tendency of convicted individuals to opt for subsidiary imprisonment rather than paying restitution, which undermines the effective recovery of state financial losses. Furthermore, inconsistencies in interpretation between prosecutors and judges, weak asset tracing mechanisms, and ambiguities in existing regulations exacerbate the problem. This study examines the legal significance of restitution in corruption cases, identifies the shortcomings in its current implementation, and proposes a ius constituendum model to reconstruct the restitution system to enhance substantive justice and improve state financial recovery. The research employs a normative juridical method, combining statutory analysis, doctrinal review, and case studies, complemented by a comparative study of legal frameworks in the United States and the United Kingdom to highlight gaps in Indonesia’s asset recovery mechanisms. The findings indicate that first, current regulations fail to provide adequate deterrence; second, there is insufficient alignment between state interests and the rights of convicts; and third, existing mechanisms for asset tracing and execution are ineffective. Accordingly, this study recommends legal reconstruction through strengthening the prosecutorial role in execution, ensuring consistency between prosecution demands and judicial decisions, and incorporating the time value of money in determining restitution amounts.